Agronomic value of metal complexes with organic acids and nutritional effects of iron sources in plants - Justi, Marina (2020)
Complexing agents are largely used for agricultural and environmental applications. For years, synthetic aminopolycarboxilic acids, such as EDTA, have been the most common complexing agents used for these applications. However, aminopolycarboxylic acids are expensive and hardly degraded in the environment. Thus, the investigation of natural molecules that can act as complexing agents is essential for sustainable applications. This study aimed at understanding the chemical properties of complexes formed between several metals and low-molecular-weight organic acids, and testing some of these complexes for agricultural applications. Complexes were synthesized at pH 7 using metals Fe, Mn, and Zn, as well as citric, tartaric, malic, and oxalic acids as complexing agents. The 1:1 and 1:2 stoichiometric ratios of reaction (SR; metal: ligand molar ratio) were tested. The chemical species formed were determined through VISUAL Minteq software. Molecular structure and stability were determined through theoretical calculations, and the complexes were submitted to the Fourier Transformed Infrared Spectra (FTIR analysis). The chemical characterization showed that complexed metal fraction, stability, and solubility depended on reaction stoichiometry, metal type, and complexing agent type. Oxalic acid was the smallest molecule used, and its complexes were predominantly of the 1:2 stoichiometry, presenting very low solubility and high stability. Citric and malic acid formed highly soluble complexes. Malic acid only formed 1:1 stoichiometry complexes with all metals and both stoichiometries tested. Citric and tartaric acid tended to form 1:2 complexes with Zn and 1:1 complexes with Mn and Fe. Considering the metals tested, the Fe complexes were more stable than Mn and Zn complexes. The chemometric partial least square technique was used to test the possibility to predict complex properties from spectra. Solubility and complexed-metal fraction were adequately predicted from FTIR spectra. The use of iron complexes as Fe sources in foliar application to maize and nutrient solution addition to soybean and maize was tested in greenhouse experiments. Foliar application of Fe-tartrate and Fe-citrate at 1:2 SR promoted similar plant growth and better Fe nutrition than the application of Fe-EDTA and FeSO4. When applied in the nutrient solution, iron-organic acid complexes kept less iron in the complexed form than EDTA. The effectiveness of complexes in promoting Fe accumulation and plant growth depended on plant species. Despite showing low complexation capacity, the Fe-tartrate at 1:2 SR promoted suitable Fe nutrition in maize plants. As for soybean, Fe-oxalate complexes promoted growth and Fe accumulation in plants similarly to that of the Fe-EDTA treatment.